Reality of Jordanian Public Policies in Fighting Terrorism From the Point of View of the Political Science Professors - Al-Thubetat, Dr. Qasem Jamil; Al-Dajah, Dr. Hasan Abdullah; almseidin, Dr. Yousef salameh (Opción, 1970)
The study discussed the reality of Jordanian public policies in fighting terrorism from the point of view of political science professors, which is through two axes: the first axis is theoretical, but the second axis is the field one. The study also employed the descriptive analytical approach, and through distributing a questionnaire on a purposed sample of the political science teaching staff members in the Jordanian universities. The study also cleared that there exist differences in trends of the study sample about role of legislative policies in confronting terrorism due to sex variable, and there exist differences among levels of age variables in public policies in confronting terrorism